The use of muscle lipids and fatty acids to assess shark diet and condition. Issue 2 (16th November 2020) - Meyer, Lauren; Chambers, Sherrie; Gervais, Connor; Pethybridge, Heidi; Beckmann, Crystal; Bruce, Barry; Huveneers, Charlie
Abstract: Following a lack of detected change in white shark Carcharodon carcharias L. 1758 diet and nutritional condition attributed to the interaction with the cage‐diving industry, Lusseau and Derous ( Tourism Management, 2019, 75, 547–549) cautioned the use of muscle lipids and fatty acids in this context, advocating for other biomarkers. This study provides additional evidence from peer‐reviewed literature to contend the usefulness of elasmobranch muscle fatty acid profiles to detail diet and habitat use. It also presents findings from a controlled experiment on captive Port Jackson sharks Heterodontus portusjacksoni (Meyer 1793) whereby long‐term (daily for 33 days) 3 min exhaustive chase exercise changed muscle lipid class profiles, supporting its use to infer nutritional condition after activities such as interactions with wildlife tourism operators. Conversely, the unaltered muscle fatty acid and lipid content suggests their use in trophic ecology is not confounded by activities such as interacting with tourism operators, remaining useful biomarkers to investigate diet and habitat use.